Measuring Smart Building Readiness Index: A Case Study of Bandung City - Indrawati .; Angdini Nurillaily; Husni Amani; S. K. B. Pillai (Jurnal Manajemen Indonesia, 2020)
Government and private players started focusing on developing cities in to smart cities due to increased level of urbanization in most of the countries around the world, including in Indonesia, by focusing on developing new smart buildings and upgrading old ones. Present paper tried to find out the Smart Building Readiness Index (SBRI) of Bandung City for knowing the level of awareness among the general public based on an exploratory research, the result of which enables the authorities to take strategic initiatives for improving the smart buildings and then to smart city status. Required data was collected by conducting in-depth interviews with 30 respondents and the result of the qualitative data revealed that Bandung’s SBRI comes to only 64.39, which is not a good indicator but within the limits of fairness and needs lot of improvement in future. The result also can be considered as an indicator that annual energy consumption in Bandung city is still at a high level and needs to focus on improving the quality of buildings in and around Bandung city for the purpose of overall reduction in energy consumption and improvement in quality of environment as well as quality of life. Respondents are also not fully aware of the smart building concept. Much needs to be done for making the public aware of the concept of smart building and its usefulness along with strategically developing smart buildings so that in future Bandung city transforms into a smart city with smart buildings. Keywords— Smart City; Smart Building Readiness Index; Bandung.